Study to evaluate the relationship between receptor expression and clinical parameters in subjects with glioblastoma - K Ashwini; Jayaprakash Shetty; Kishan Prasad; Shilpa S Shetty; Ananthan Raghotham; Vijith Shetty; Praveen Kumar Shetty; N Suchetha Kumari (Biomedical and Biotechnology Research Journal, 2023)
Background: The most frequent and most aggressive primary brain tumor, glioblastoma (GBM) has an extremely poor prognosis. Several studies have shown the involvement of sex hormonal receptors and growth factor receptors in the onset of GBM. Recent research has highlighted the importance of inflammatory biomarkers as useful prognostic indicators and survival outcome predictions in several cancer. Based on pretreatment blood tests, the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), eosinophil-to-lymphocyte ratio (ELR) have been investigated as potential indicators of prognosis in cancer patients. The aim of the present study was to evaluate the expression of androgen receptor (AR), estrogen receptor (ER), and epidermal growth factor receptor (EGFR) in the GBM tissue blocks and to correlate NLR, PLR, and ELR with clinical parameters. Methods: Receptor expression in the tissue sample was screened by immunohistochemistry. Clinical data of these patients were collected from clinical records and NLR, PLR, and ELR were calculated. Results: The present study showed increased expression of EGFR in the screened sample. We grouped receptor-expressing groups as EGFR expressing group and others (AR and EGFR, ERα). Statistically significant difference in the distribution of neutrophils, lymphocytes, and serum glutamic-oxaloacetic transaminase (SGOT) level was found between the EGFR and other groups. Statistically significant positive correlation was found between NLR and SGOT and serum glutamic-pyruvic transaminase (SGPT). Statistically significant positive correlation was found between TLC, SGOT with PLR and statistically significant negative correlation was found between hemoglobin and PLR. Statistically significant positive correlation was found between SGOT, SGPT, and ELR. There was no significant correlation found between the position of the tumor and size of the tumor with clinical parameters. Conclusions: These blood biomarkers along with receptor expression should gain more importance in predicting therapy and improving overall survival in GBM patients.